Microfinance banks and rural development—The Nigeria experience. (2014)
The Central Bank of Nigeria (CBN) launched the microfinance banking scheme on December 2005 as part of government strategies to achieve one of the cardinal agendas of the Millennium Development Goals (MDGs) of reducing extreme poverty by 2015. The microfinance banks (MFBs) were promoted to provide financial services to the economically active poor in the society and to create an environment of financial inclusion to boost the capacity of micro, small and medium enterprises that abound in our rural areas. The impact of the MFBs in rural development in Nigeria was empirically evaluated in this study using some performance indicators. These include growth in deposit mobili¬zation, aggregate credit extension, loan per rural person (LPRP), total assets of MFBs, etc. The ordinary least square econometrics was used to generate the regression coefficients and other statistics. Data for the study were gath¬ered from the Annual Report and Accounts published by the MFBs and collated and analyzed by the CBN in the Statistical Bulletins. The impetus for the study waslargely derived from the renewed interest in microfinancing by the World Bank, International Development Institutions, the Nigerian Government and other International Development Partners. The results of the study show that MFBs have impacted positively on our rural economy. The regression coeffi¬cients for all the key factors analyzed in the research were positive though not statistically significant. This means that the full impact possibilities of these insti¬tutions as catalyst for rural development are yet to be realized. The findings also provide significant support to the rationale earlier canvassed by the CBN for the recent re-engineering of the various microfinance institutions in the country in order to improve their impact possibilities. The researchers noted that the recent re-engineering and retooling of the MFBs scheme is one step in the right direction and recommends that government should provide key infrastructures especially electricity and ensure stable macroeconomic environment to enable micro and other business enterprises to thrive in the country.